HMF and diastase activity in honeys: A fully validated approach and a chemometric analysis for identification of honey freshness and adulteration. (15th August 2017) - Pasias, Ioannis N.; Kiriakou, Ioannis K.; Proestos, Charalampos
Graphical abstract: Highlights: Hydroxymethylfurfural and diastase were determined in honeys using fully validated methods. Calculation of the methods' uncertainty was performed. Chemometric analysis was performed. Hydroxymethylfurfural and diastase can be considered as freshness indicators. Abstract: A fully validated approach for the determination of diastase activity and hydroxymethylfurfural content in honeys were presented in accordance with the official methods. Methods were performed in real honey sample analysis and due to the vast number of collected data sets reliable conclusions about the correlation between the composition and the quality criteria were exported. The limits of detection and quantification were calculated. Accuracy, precision and uncertainty were estimated for the first time in the kinetic and spectrometric techniques using the certified reference material and the determined values were in good accordance with the certified values. PCA and cluster analysis were performed in order to examine the correlation among the artificial feeding of honeybees with carbohydrate supplements and the chemical composition and properties of the honey. Diastase activity, sucrose content and hydroxymethylfurfural content were easily differentiated and these parameters were used for indication of the adulteration of the honey.